2020
DOI: 10.1016/j.desal.2019.114230
|View full text |Cite
|
Sign up to set email alerts
|

Multistage pressure-retarded osmosis configurations: A unifying framework and thermodynamic analysis

Abstract: Pressure-retarded osmosis has enjoyed increasing research interest over the last decade. Recent studies focusing on single-stage PRO designs have raised doubts regarding the long-term economic viability of the technology. While most of the analyses are based on single-stage operation, comprehensive analysis of multistage PRO which shows promise for better energetic performance is absent. Previous studies on multistage PRO differ in their design philosophies and performance metrics, leading to an incomplete ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…The multistage process is widely applied in desalination to avoid a large entropy generation and significant thermal disequilibrium in a single-stage process. In particular, entropy generation (and excessive energy consumption) in electromembrane processes (ED and ICP) increases in a nonlinear fashion with current, due to new current carrier generation, membrane discharging by the thicker depletion layer, trans-membrane concentration difference leading to osmosis and diffusion, and electro-osmosis. It is therefore challenging to optimize the staging configuration toward the proper trade-off between productivity (needed for a small-size membrane) and energy efficiency (needed for a small-size battery) ,, without engineering models for unit processes. Several physics-based models, solving Nernst–Planck–Poisson and Navier–Stokes equations concurrently, have already been developed to describe ion transport mechanisms of a conventional electromembrane process (i.e., ED); however, they are limited to operating in an ohmic regime where voltage drop and ion transport respond linearly with changes in current. , Also, simulation-based surrogate models based on machine learning methods were applied to predict ED processes, treating brackish water (2–10 mM of salt) for which ion-exchange membranes could retain their ideal permselectivities. , However, these earlier models for the electromembrane process are not adequate for our purpose, where small-size electromembranes push the operating current beyond the Ohmic regime.…”
Section: Resultsmentioning
confidence: 99%
“…The multistage process is widely applied in desalination to avoid a large entropy generation and significant thermal disequilibrium in a single-stage process. In particular, entropy generation (and excessive energy consumption) in electromembrane processes (ED and ICP) increases in a nonlinear fashion with current, due to new current carrier generation, membrane discharging by the thicker depletion layer, trans-membrane concentration difference leading to osmosis and diffusion, and electro-osmosis. It is therefore challenging to optimize the staging configuration toward the proper trade-off between productivity (needed for a small-size membrane) and energy efficiency (needed for a small-size battery) ,, without engineering models for unit processes. Several physics-based models, solving Nernst–Planck–Poisson and Navier–Stokes equations concurrently, have already been developed to describe ion transport mechanisms of a conventional electromembrane process (i.e., ED); however, they are limited to operating in an ohmic regime where voltage drop and ion transport respond linearly with changes in current. , Also, simulation-based surrogate models based on machine learning methods were applied to predict ED processes, treating brackish water (2–10 mM of salt) for which ion-exchange membranes could retain their ideal permselectivities. , However, these earlier models for the electromembrane process are not adequate for our purpose, where small-size electromembranes push the operating current beyond the Ohmic regime.…”
Section: Resultsmentioning
confidence: 99%
“…Yang et al 32 report an ideal maximal power density of 30 w/m 2 for the countercurrent PRO system. Chung et al 33 reported a net power density of 7.3 w/m 2 using a 10-Stage PRO countercurrent system, while Song et al 34 reported a gross power density of 21.3 w/m 2 . These power densities are lower than the theoretical generation of 48.5 w/m 2 obtained in this work for configuration 5 with a low-salinity feed for the PRO of 1000 ppm.…”
Section: Resultsmentioning
confidence: 99%
“…The distribution of feed flow rate and membrane area were important factors to average power density. Multistage PRO (10-stage PRO) increased net power density around 9% higher than a single-stage PRO with the same membrane area [8]. Thus, a two-stage PRO is proposed to reduce this effect and improve the overall performance in terms of power density.…”
Section: Introductionmentioning
confidence: 99%